A critical appraisal of safety data on dydrogesterone for the support of early pregnancy: a scoping review and meta-analysis. Issue 2 (August 2022) - Katalinic, Alexander; Shulman, Lee P.; Strauss, Jerome F.; Garcia-Velasco, Juan A; van den Anker, John N.
Abstract: No data support the suggestion that first-trimester dydrogesterone use increases the risk of fetal abnormalities; however, two low-quality retrospective studies (one retracted by the journal) have suggested such a link. A scoping review and meta-analysis were carried out to address this discrepancy. The literature was reviewed but it was not possible to identify any evidence of a plausible mechanism for potential causality between dydrogesterone and fetal abnormalities. To investigate whether any evidence existed, a preliminary meta-analysis was undertaken of clinical studies published since 2005 on first-trimester dydrogesterone use with assessment of fetal abnormalities. A fixed effects model was used to determine pooled odds ratios with 95% confidence intervals (95% CI). From 83 articles identified, six randomized controlled trials were included. Pooled risk ratios (RR) for maternal dydrogesterone use and fetal abnormalities gave a RR approaching 1 (RR 0.96; 95% CI 0.57, 1.62), confirming previous conclusions of no causal association between fetal abnormalities and first-trimester dydrogesterone use. Physicians, scientists and journal reviewers should exercise due diligence to prevent promulgation of retracted data. We are confident in using dydrogesterone, if indicated, in the treatment of threatened or recurrent miscarriage, and believe that its favourable safety profile should extend to its appropriate use in assisted reproductive technologies.